Attitudinal Language of Flora and Fauna Discourse on an Indonesian Tourism Website: Appraisal in Ecolinguistics - Arina Isti'anah (Master Program in Linguistics, Diponegoro University, 2021)
This paper reports the appraisal analysis - particularly the attitudinal language - of Indonesian flora and fauna discourse on the official website of Indonesian tourism by examining 11 articles, accessed on www.Indonesia.travel. This paper qualitatively identifies the appraised features denoting Indonesian flora and fauna discourse and examined their appraising resources by applying Martin & White’s (2005) framework. Through the lens of interpersonal meaning, this paper criticizes how the website communicates through flora & fauna discourse in tourism to global readers. Findings reveal that affect, judgement, and appreciation function in several ways: introduce Indonesian endangered and endemic species, present the government’s seriousness to preserve the species, and promote the happiness and satisfaction tourists can feel when visiting the sites. From an ecolinguistics point of view, the website presents a beneficial discourse since it does not focus on feelings the tourists may have but the appreciation of the natural phenomena.